The Slow Demographic Transition in Regions Vulnerable to Climate Change - Thang Dao; Matthias Kalkuhl; Chrysovalantis Vasilakis (Institute of Labor Economics (IZA), 2022)
We consider how the demographic transition has been shaped in regions that are the least developed and the most vulnerable to climate change. Environmental conditions affect intra-household labor allocation because of the impacts on local resources under the poor infrastructural system. Climate change causes damage to local resources, offsetting the role of technological progress in saving time that women spend on their housework. Hence, the gender inequality in education/income is upheld, delaying declines in fertility and creating population momentum. The bigger population, in turn, degrades local resources through expanded production. The interplay between local resources, gender inequality, and population, under the persistent effect of climate change, may thus generate a slow demographic transition and stagnation. We provide empirical confirmation for our theoretical predictions from 44 Sub-Saharan African countries.
Keywords: J11; J16; Q01; Q20; Q54; Q56; 330; climate change; local resources; fertility; gender inequality in education; slow demographic transition